2019
DOI: 10.1109/tpel.2018.2858443
|View full text |Cite
|
Sign up to set email alerts
|

DC–DC Boost Converter With a Wide Input Range and High Voltage Gain for Fuel Cell Vehicles

Abstract: In fuel cell vehicles, the output voltage of the fuel cell source is typically much lower than the voltage required by the DC bus and also this output voltage drops significantly as the output current increases. In order to match the output voltage of the fuel cell source to the DC bus voltage, a new DC-DC boost converter with a wide input range and high voltage gain is proposed to act as the required power interface, which reduces voltage stress across the power devices and operates with an acceptable convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(81 citation statements)
references
References 33 publications
2
79
0
Order By: Relevance
“…It can be observed that the proposed converter requires lower number of diodes and capacitors as compared with previous studies. 12,28,29,35 The number of capacitors required in proposed converter is more than that of Lou and Ye 30 but has lower number of inductors and lower voltage stress on its components than that of Lou and Ye. 30 Therefore, the proposed converter provides a good trade-off among voltage conversion ratio, number of components, and the current and voltage stress as compared with other topologies.…”
Section: Current Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that the proposed converter requires lower number of diodes and capacitors as compared with previous studies. 12,28,29,35 The number of capacitors required in proposed converter is more than that of Lou and Ye 30 but has lower number of inductors and lower voltage stress on its components than that of Lou and Ye. 30 Therefore, the proposed converter provides a good trade-off among voltage conversion ratio, number of components, and the current and voltage stress as compared with other topologies.…”
Section: Current Stressmentioning
confidence: 99%
“…8,9 In order to get a high voltage conversion ratio with reduced duty cycle, various topologies have been presented. [10][11][12][13][14][15][16][17] These topologies can be broadly classified into two categories: magnetic-based and magnetic-less converter. A transformer or coupled inductor-based converter can achieve high voltage gain by increasing the turns ratio without the use of excessive duty cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The low output voltage of energy sources in DC microgrids necessitates application of high-gain single-input single-output (SISO) or multiple-input single-output (MISO) DC-DC converters. [3][4][5][6][7] Three high step-up MISO converters have been presented in previous studies [3][4][5] that take the advantages of modularity, continuous input current, low blocking voltage (BV) on semiconductors and semibidirectional power flow capability. Incapability of direct power transfer from upper order units to the load as well as large current stress (CS) of T 1,1 switch are the main drawbacks of these previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Incapability of direct power transfer from upper order units to the load as well as large current stress (CS) of T 1,1 switch are the main drawbacks of these previous studies. [3][4][5] The study of Zhang et al 6 presents a unidirectional SISO converter that adopts a diodecapacitor voltage lift cell to produce high step-up capability. Also, another study 7 presents a detailed review of voltage lift methodologies in SISO DC-DC converters.…”
Section: Introductionmentioning
confidence: 99%
“…LEAN energy resources such as photovoltaic (PV) and fuel cell (FC), exhibit low unregulated output voltage, which requires a dc-dc converter with a high voltage step-up ratio [1]- [6]. Several approaches including inductive switching (e.g.…”
Section: Introductionmentioning
confidence: 99%